SOCIOCULTURAL LANDSCAPE OF RURAL COMMUNITY IN NEW TOWN DEVELOPMENT OF BUMI SERPONG DAMAI CITY KOTA TANGERANG SELATAN, INDONESIA - Wahid, Alvin Gus Abdurrahman; Widyawati, . (PEOPLE: International Journal of Social Sciences, 2018)
Bumi Serpong Damai City, a New Town Development in Kecamatan (District) Serpong, Kota Tangerang Selatan, Indonesia, is causing many changes in land usage in its development area and also a flow of immigrants into this area. This phenomenon is causing rural settlement or kampung in this area to change in terms of land usage and population proportions, this kampung, namely Lengkong Ulama, is culturally very rich in traditional religious activities and education. The mentioned changes are affecting the social condition in communal and gathering activities within the kampung and can be explained by its spatial organization across generations. Methods in data gathering and data analysis in this research are done by qualitative methods, by using in-depth interview with snowballing sampling. Lengkong Ulama keeps it cultural value by having some strong Islamic institutes throughout generations and have a consistent gravitational system of notable places such as mosque and tomb, which creates a place identity in the village.